Men, Masculinities and Religious Change in Twentieth-Century Britain - Delap, L.; Delap, L.; Morgan, S.; Morgan, S. (Genders and Sexualities in History,, 2013)
Charting the growing religious pluralism of British society, this book investigates the diverse formations of masculinity within and across specific religions, regions and immigrant communities. Contributors look beyond conventional realms of worship to examine men's diverse religious cultures in a variety of contexts.